Evaluation Of Service Quality For Undergraduate Programs At Andalas University - Putri, Nilda Tri; Broto Adi, Alexie Herryandhi; Fikri, Ryan Kamal (Universitas Katolik Parahyangan, 2017)
Total Quality Management is a philosophy and key to bring success in the industry for this era. Total Quality Management plays an important role in the management system and culture to create or produce a good products and service. Andalas University is one object of the application of Total Quality Management in the education sector. Research carried out aims to describe the service quality for undergraduate programs at the Andalas University. Based on the measurement of the service quality, obtained the information related to the level of student satisfaction each Departments and priority improvements to service variable. The study used a questionnaire with two instrument ratings. The instruments rating are an assessment of the level of service and service priority. The calculation for service quality used CSI (Customer Satisfaction Index) method. The recommendations for improve service quality used IPA (Importance Performance Analysis) Method. Based on research conducted, service quality Undergraduate Program at Andalas University can be categorized as low. It was based on the value of CSI located on the 4th lowest category, which is one of courses in Very Poor category, 9 courses in Poor category, 3 courses in the Cause for Concern category, and 1 course on Borderline category. While the dimensions of which are in the service of a general improvement priorities is the Tangible and Reliability dimension.